German visual dictionary - Reid, Lauren; Stevenson, Anna; Zimmermann, Silke (Collins, 2019)
The home of trusted full-colour visual dictionaries for everyday use. A photographic guide to the key words and phrases in German. This attractive pocket-sized book is a perfect travel companion and provides a practical guide to Germany and German language and culture.